(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Women’s higher education helps in moving the family and society in higher place and developed the nation in better future and also makes a vital contribution to sustainable development through the generation and dissemination of knowledge. Research questions were formed depending on three specific objectives. Qualitative method was used in this study. Major findings were framed according to the objectives and researcher found that so many problems they faced; finally two case studies have done to know the journey in higher education.